Semi-autonomous revenue authorities for successful implementation of tax administration reform - Ghebretsadk, A. F. (Abraham Fissehaye) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPA)--University of Stellenbosch, 2003.